COMPLEX THERAPY EFFECT ON THE STATUS OF THE CHILDREN'S KIDNEYS WITH THE VESICOURETERAL REFLUX IN THE POST OPERATION PERIOD - V.I. Kirillov; V.I. Runenko; N.A. Bogdanova; S.A. Mstislavskaya ("Paediatrician" Publishers LLC, 2007)
The medical strategy to address the vesicoureteral reflux is a very urgent issue in the children's nephrology. Based on the examination of 44 children with the iii-iv degree vesicoureteral reflux, aided by the complex of laboratory, functional and instrumental methods, the authors have analyzed the effect of the combined plant medication (Canephron N, Bionorica AG, Germany) on the short and long term outcomes of the antireflux operations. They have established that introduction of the medication into treatment leads to the term increase of the kidney resetting and urinary syndrome related to the inflammatory process inclusive. Key words: vesicoureteral reflux, antireflux operations, urodynamics disorders, tubular dysfunctions, combined plant medication, children.